Intoxicação por Senecio spp. : padrões morfológicos hepáti-cos em bovinos e resistência adquirida em ovinos - Grecco, Fabiane Borelli (2009)
This study him to characterize liver morphological patterns of the intoxication by Senecio spp. observed in cattle in Southern Rio Grande do Sul State, Brazil between 2000-2008 and to text the acquireal resistance in sheep to Senecio brasiliensis poisoning. The patterns observed were correlated with climate changes occurred in the period. Two outbreaks Senecio spp. In sheep were described. It was tested if repeated doses of S. brasiliensis induce resistance to the intoxication in sheep. The macroscopic and histological lesions of cattle dead by Senecio spp. toxicosis submitled to Regional Diagnostic Laboratory of Pelotas University were analyzed. The lesions were classified in seven different patterns. The outbreaks prevalence and climate changes concerning accumulated rain and temperature mean in different seasons of year were analyzed. To determine if repeated doses of S. brasiliensis induce resistance to the intoxication in sheep, doses that cause acute intoxication was determined. The green plant was administered by gavage to 3 sheep in doses of 60, 80, 90 and 100 g/kg of body weight (bw). The doses (100g\kg of bw) that caused acute poisoning were divided in 2, 5 and 10 doses and administered daily in 2, 5 and 10 days to observe if chronic lesion would develop. Sheep that received 10g/kg of bw was challenged with 100g/kg of bw after 45 days the last doses of 10g. Doses of 15 g/kg of bw were administered by gavage for 30 days and 10 g/kg of bw for 10 days to three sheep. Two of them were challenged 24 hours after the last doses of 30g/kg of bw. One sheep was challenged 15 days after the last doses of 30g/kg of bw. The results of macroscopic and histological analyze of liver showed that the diffuse liver fibrosis and nodular regeneration were the most common lesions induced by Senecio spp. intoxication in cattle. Although between 2007 and 2008 the pattern with little fibrosis and histological subacute lesion had been observed. In outbreaks of spontaneous Senecio spp. poisoning in sheep jaundice, photodermatitis, progressive emaciation and death in 4 to 30 days were observed. Macroscopic lesion were characterized by jaundice, yellowish liver, mesentery edema, ascitis, alternativaly dark and firm liver with numerous small well-circumscribed nodules measuring 1-5mm in diameter in the cut and capsular surface. Microscopically the hepatic lesions were similar in all affected sheep and characterized by hepatomegalocytosis, periportal fibrosis, hepatocytes necrosis and biliary ductal proliferation. The results of experimental intoxication showed that doses up 90g/kg of bw cause acute intoxication and the doses of 100g/kg of bw divided in10 doses do not induces resistance to Senecio brasiliensis poisoning in sheep. It was demonstrated that 15g/kg of bw for 30 days and 30g/kg of bw for 10 days induce resistance to Senecio basiliensis poisoning if the animals were challenged with 100g/kg of bw immediately after last dose of 30g/kg of bw and lost resistance after 15 days.